Factors affecting BIM implementation in post-conflict low-income economies: the case of Afghanistan - Al-Mohammad, Mohammad; Ahmad Tarmizi, Haron; Mohammad Numan, Aloko; Rahimi, A. Rahman (Emerald Publishing Limited, 2021)
Purpose Rejecting building information modeling (BIM) can negatively impact the architectural, engineering and construction (AEC) industries. While BIM is trending globally, its implementation in post-conflict low-income economies is still limited. The purpose of this paper is to identify the critical factors for implementing BIM in a post-conflict low-income economy, using Afghanistan as a case study.